2023
DOI: 10.1037/bne0000542
|View full text |Cite
|
Sign up to set email alerts
|

A history of ethanol intake accelerates the development of morphine analgesic tolerance: A protective potential for omega-3 fatty acids.

Abstract: Adolescence is a critical life period during which significant neurodevelopmental changes occur within the central nervous system. Consistently, substance abuse in this stage has been found to induce persistent changes in brain responsiveness to future drug challenges. Nowadays, heavy episodic alcohol consumption during adolescence, also known as binge-drinking behavior, is a growing concern in modern societies. On the other hand, alcohol is well known to act as a gateway drug, that is, it promotes the individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…In is now well-established that both nicotine and alcohol abstinence following prolonged intake impairs various dysfunctions with a marked adverse effect on learning and memory 33 , 44 , 45 , 59 , 60 . Studies on human populations have revealed that nicotine-alcohol interaction further complicates the post-quit behavioral outcomes, therefore, finding therapeutic or ameliorative strategies are of paramount significance 61 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In is now well-established that both nicotine and alcohol abstinence following prolonged intake impairs various dysfunctions with a marked adverse effect on learning and memory 33 , 44 , 45 , 59 , 60 . Studies on human populations have revealed that nicotine-alcohol interaction further complicates the post-quit behavioral outcomes, therefore, finding therapeutic or ameliorative strategies are of paramount significance 61 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, O 3 treatment was done from PNDs 21 to 63 in parallel with behavioral tests. It should be mentioned that O 3 doses were chosen based on our previous studies (Ahmadi-Soleimani, Amiry, et al, 2023;Ahmadi-Soleimani, Azizi, et al, 2023;Amiry et al, 2023). The rats were randomly divided into six groups (n = 10 per group) and treated as follows:…”
Section: Study Protocol For Animal Model Of Ethanol Exposure and Expe...mentioning
confidence: 99%